High prevalence of resistance to macrolides and fluoroquinolones in Mycoplasma genitalium isolated from patients in two Russian megalopolises – Moscow and St. Petersburg in 2021– 2024 - Edelstein I.A.; Gushchin A.E.; Gladin D.P.; Romanov A.V.; Negasheva E.S.; Frigo N.V.; Kozlov R.S.; Potekaev N.N.; Kozlova N.S.; Borukhovich D.G. (Клиническая микробиология и антимикробная химиотерапия)
Objective.